A Two-Step Strategy for the Rapid Enrichment of Nitrosocosmicus-Like Ammonia-Oxidizing Thaumarchaea - Liu, Liangting; Li, Surong; Han, Jiamin; Lin, Weitie; Luo, Jianfei (Frontiers in Microbiology, 2019)
Ammonia-oxidizing archaea (AOA) are widely distributed on the earth and play a significant role in the global nitrogen cycle. Although dozens of AOA strains were obtained in the last 13 years, it is still necessary to obtain more AOA strains for the entire exploration of their ecology, physiology, and underlying biochemistry in different environments. In this study, we designed a two-step strategy for the rapid enrichment of Nitrosocosmicus–like AOA from soils. Firstly, combination of kanamycin and ampicillin was chosen as the selective stress for bacteria and quartz sands were used as the attachment of AOA cells during the first step cultivation; only after 40–75 days cultivation, AOA enrichments with abundance >20% were obtained. Secondly, combination of ciprofloxacin and azithromycin was chosen as the selective stress for the following cultivation; it is able to penetrate the biofilms and kill the bacterial cells inside the aggregate, contributing to the AOA enrichments reached high abundances (90%) only after one-time cultivation. Basing on this strategy, three AOA strains were obtained from agricultural soils only after 90–150 days cultivation. Phylogenetic analysis suggested these AOA belong to the soil group I.1b Thaumarchaeota and are closely related to the genus Nitrosocosmicus. In general, AOA enrichment or isolation is very difficult and time-consuming (an average of 2–3 years). Here, we provide a new strategy for the rapid enrichment of high abundance of Nitrosocosmicus-like AOA from soil, which gives a new solution to the AOA enrichment and cultivation in a short period.